2005
DOI: 10.1002/cncr.21560
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic features of endometrial carcinoma associated with HNPCC

Abstract: BACKGROUNDEndometrial carcinoma is a common malignancy in hereditary nonpolyposis colorectal carcinoma (HNPCC). Like colon carcinoma, endometrial carcinoma is diagnosed at an earlier age in women with HNPCC. In contrast to colon carcinoma, the pathologic features of endometrial carcinoma in HNPCC have not been studied in detail. It was the purpose of this study to pathologically characterize a series of HNPCC associated endometrial carcinomas.METHODSFifty women with HNPCC and endometrial carcinoma were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
193
3
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 38 publications
13
193
3
6
Order By: Relevance
“…1 These morphological features suggest that some undifferentiated carcinomas derive from endometrioid endometrial carcinomas and that molecular changes characteristic of endometrioid tumors are likely to be found in undifferentiated endometrial carcinomas. In this regard, we confirmed previous observations 1,17 by demonstrating that the presence of DNA mismatch repair abnormalities was characteristic of undifferentiated endometrial carcinomas. This molecular alteration has been observed in 20-30% of EECs in a different series 18 and it was present in nearly 40% of undifferentiated endometrial carcinomas in the present series.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1 These morphological features suggest that some undifferentiated carcinomas derive from endometrioid endometrial carcinomas and that molecular changes characteristic of endometrioid tumors are likely to be found in undifferentiated endometrial carcinomas. In this regard, we confirmed previous observations 1,17 by demonstrating that the presence of DNA mismatch repair abnormalities was characteristic of undifferentiated endometrial carcinomas. This molecular alteration has been observed in 20-30% of EECs in a different series 18 and it was present in nearly 40% of undifferentiated endometrial carcinomas in the present series.…”
Section: Discussionsupporting
confidence: 91%
“…Although this series comprised 16 tumors previously analyzed, the frequency of mismatch repair abnormalities in new cases (40% or 2/5) was similar to that of the prior study (37% or 6/16). Mismatch abnormalities in undifferentiated endometrial carcinomas were first reported in sporadic tumors 17 and it was subsequently observed that undifferentiated endometrial carcinomas can also occur in Lynch syndrome. 1 In the present series, one patient showed loss of MSH2 and MSH6 expression in her undifferentiated endometrial carcinoma and is considered to be a presumptive Lynch syndrome patient.…”
Section: Discussionmentioning
confidence: 98%
“…According to these studies, risk factors are partially shared in sporadic and hereditary EC, since the BMI appeared not to have an effect on EC risk, although parity, longer use of hormonal contraceptives and a later age at menarche reduced the risk of EC in LS women (19,20). It has been suggested that LS women have more non-endometrioid tumors compared with sporadic patients, which could at least partly explain certain of the differences in the reported risk factor profiles (19)(20)(21). LS mutation carriers in the present study used hormonal contraceptives more frequently than non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…OCPs decrease endometrial and ovarian cancer risks in the general population by approximately 50%, [34][35][36][37][38][39][40][41][42][43] and progestin intrauterine devices may reverse hyperplasia and early endometrial cancer. 44,45 Because Lynch syndrome-associated gynecologic cancers appear to be similar to sporadic cases, 4,46 these chemoprevention strategies may be beneficial with less adverse effect on quality of life than prophylactic surgery. Our group recently completed accrual to an endometrial cancer chemoprevention study comparing OCPs and Depo-Provera for women with Lynch syndrome, and data analysis currently is ongoing.…”
Section: Discussionmentioning
confidence: 99%